TO INCREASE STUDENTS' CURIOSITY IN ELEMENTARY GRADE MATH LESSONS - Xudoyberganov Nodirjon Shokirjonovich (Bright Mind Publishing, 2026)
This article analyzes effective methods and pedagogical approaches to increase students' interest in science in primary grade mathematics lessons. In mathematics education, the importance of interactive methods, game technologies, teaching on the basis of problem situations and the use of modern information technologies are highlighted. Also provides methodological recommendations for choosing tasks appropriate to the age characteristics of students, forming motivation, developing creative thinking and increasing activity in the learning process. The results of the research are significant as they serve to enrich the content of primary school mathematics lessons and to form strong knowledge and stable interest in students.
Keywords: Primary education, mathematics lesson, student motivation, interest, interactive methods, game technologies, didactic materials, creative thinking, modern pedagogy, quality of education.